Analisis Kekerasan Pada Anak Berdasarkan Hadits Dan Undang-Undang No. 35 Tahun 2014 - Naufal Albara Safadar; Tajul Arifin (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research aims to determine the prevalence of cases of violence against children based on hadith and law no. 35 of 2014. Violence against children is a serious problem that affects children's welfare and development. This article presents an analysis of violence against children based on the hadith perspective and Law no. 35 of 2014 concerning Child Protection. Through a literature review, this article describes the concept of violence against children according to Islamic teachings as well as the legal perspective regulated in Law no. 35 of 2014. Apart from that, this article also discusses the impact of violence on children and prevention efforts that can be taken from both a religious and legal perspective. It is hoped that this article can provide deeper insight into child protection in the context of violence and provide a basis for efforts to overcome violence against children in society.